Optimization of devulcanization process of waste rubber product by thiobacillus ferrooxidans - Ainie Asyikin, Ahmad; Faridah, Yusof; Shuhaida, Safian; Ahmad Nazree, Abdul Rahim; Anumsima, Ahmad Barkat; Khater Sharifa, Shah Ari @ Ansari (Universiti Teknologi MARA (UiTM), 2011)
International Conference on Science and Technology Applications in Industry and Education (ICSTIE 2008) organized by Universiti Teknologi MARA (UiTM), 12th - 13th December 2008 at Penang, Malaysia.